Osteosarcoma of jaw bone - Avani Gandhi Dixit; Nipa J Parikh (Wolters Kluwer Medknow Publications, 2008)
Osteosarcoma is the most common primary malignant bone tumor in children. Its radiolographic appearances vary considerably. It may show a number of presentations from onion skin or sunburst appearance. Osteosarcoma of maxilla and mandible are distinct from long bone osteosarcoma and shows a distinct clinical, histologic and prognostic characteristic that when diagnosed and treated properly have a better prognosis from the later. The present article reports a case of osteogenic sarcoma of maxillary alveolar ridge and compares it with long bones osteosarcomas.